Analisis Pengaruh Gaya Kepemimpinan, Pengawasan Kerja dan Lingkungan Kerja Terhadap Kinerja Pengawai Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Daerah Kabupaten Tapanuli Selatan - Juniarti Juniarti; Batubara, Tomi Widodo (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to find out the influence of leadership style, work supervision, and working environment toward the employees’ performance in the Civil Registry Service Office of South Tapanuli Regency. Quantitative method and approach are used together with statistical analysis via SPSS version 26. The population of this research consists of 45 employees working at the Civil Registry Service Office of South Tapanuli Regency. Probability Sampling is done through saturated census; due to the fact that the total population is less than 100 persons. The results show that leadership style has partially positive and significant influences toward the employees’ performance with an amount of tcount > ttable (3,126 > 2,01954), work supervision has positive and significant influences toward the employees’ performance with an amount of tcount > ttable (3,758 > 2,01954), and working environment has positive and significant influences toward the employees’ performance with an amount of tcount > ttable (4,759 > 2,01954). Moreover, the leadership style, work supervision, and working environment simultaneously have positive and significant influences toward the South Tapanuli Regency’s Civil Registry Service Office employees with an amount of fcount > ftable (160,475 > 2,83). The research results show that partially and simultaneously, H1 is accepted; meanwhile H0 is denied. In addition, the coefficient of determination value is 91,6%; with a residual of 8,4% from other independent variable that is purposely left out from this research.